Identification of a small molecule targeting EPLIN as a novel strategy for the treatment of pediatric neuroblastoma and medulloblastoma - Emma Lindell; Jing Guo; Miao Zhao; Natallia Rameika; Xi Lu; Tabea Wacker; Lei Zhong; Tobias Bergström; Sara Svanberg; Azazul I. Chowdhury; Peter Bergsten; Xingqi Chen; et al. (Cell Death and Disease)
Abstract Amplification of the MYCN proto-oncogene serves as a key marker of aggressive disease and poor treatment outcomes in certain pediatric tumors originating from the nervous system, including neuroblastoma and medulloblastoma. However, the complex nature of the challenging MYCN protein underscores the urgent need for additional targets and therapies to tackle neuroblastoma and medulloblastoma. In this study, with a primary focus on neuroblastoma and the aim of also benefiting children with medulloblastoma, we identified FLIX5, a small compound that exhibits broad cytotoxicity against both neuroblastoma and medulloblastoma cells, primarily by triggering apoptosis. Furthermore, FLIX5 enhances the cholesterol dependency of neuroblastoma cells under conditions where mitochondrial function is impaired. FLIX5 as well shows a synergistic effect when combined with vincristine, a conventional anticancer drug, against neuroblastoma cells and organoids. Through proteome integral solubility alteration, computational molecular docking predictions, and cellular thermal shift assays for target identification and validation, FLIX5 reveals EPLIN (Epithelial Protein Lost In Neoplasm) as a previously unexplored drug target. EPLIN is involved in several cellular processes, including cholesterol uptake and mitochondrial function. The discovery of FLIX5 targeting EPLIN presents new opportunities for treating malignant pediatric tumors, with the potential to target chemoresistant dormant cancer cells and broaden its therapeutic applications to other tumor types.